Belgica antarctica (Diptera: Chironomidae): A natural model organism for extreme environments. (28th April 2021) - Kozeretska, Iryna; Serga, Svitlana; Kovalenko, Pavlo; Gorobchyshyn, Volodymyr; Convey, Peter
Abstract: Belgica antarctica (Diptera: Chironomidae), a brachypterous midge endemic to the maritime Antarctic, was first described in 1900. Over more than a century of study, a vast amount of information has been compiled on the species (3 750 000 Google search results as of January 10, 2021), encompassing its ecology and biology, life cycle and reproduction, polytene chromosomes, physiology, biochemistry and, increasingly, omics. In 2014, B. antarctica 's genome was sequenced, further boosting research. Certain developmental stages can be cultured successfully in the laboratory. Taken together, this wealth of information allows the species to be viewed as a natural model organism for studies of adaptation and function in extreme environments. Abstract : We provide information on Belgica antarctica, which allows us to consider the species as a natural model organism to study adaptation and functioning in extreme conditions.